PENGARUH PEMBERIAN SMOOTHIES PISANG (Musa paradisiaca) DAN KURMA (Phoenix dactylifera L.) SEBELUM LATIHAN TERHADAP KELELAHAN OTOT PADA ATLET BELA DIRI DI SKOI SAMARINDA - Putri, Birgita Andrea; Utami, Riana Pangestu; Mulyani, Rieska Indah (Jurnal Gizi dan Pangan Soedirman, 2024)
Muscle fatigue was very influential on the performance of athletes during training and competition. Muscle fatigue occured due to activities that require more energy in a short time. Bananas and dates contain carbohydrates and potassium are high enough to be used to provide energy quickly and store muscle glycogen reserves. This study aims to determine the impact of banana smoothies on the index of muscle fatigue in athletes. This study used Quasi-experimental design of pre-posttest control group design. The subjects were martial arts athletes SKOI Samarinda totaling 42 people. The treatment given was to give as much as of date banana smoothies as 200 ml 60 minutes before post-test testing. Measurement of muscle fatigue index using Test Running - based Anaerobic Sprint Test (RAST). Giving date banana smoothies significantly affected the muscle fatigue index of martial arts athletes SKOI Samarinda (p<0.05). The results of bivariate analysis using Mann - Whitney test showed that there was a significant difference in muscle fatigue index of martial arts athletes SKOI Samarinda between the water treatment group and the treatment group of date banana smoothies after treatment (p<0.05). Intervention of date banana smoothies proved to be effective in preventing muscle fatigue in martial arts athletes.